The use of documentary film text in developing Arabic writing skills: what the experts say - Tg Abdul Rahman, Tg Ainul Farha; Chik, Abdul Rahman; Sahrir, Muhammad Sabri (UTM Press, 2017)
Documentary film is a language input which is based on writing skills since it consists of the introduction to subject, presentation of ideas, and conclusion of subject. Many studies have highlighted the linguistic, informational, and pedagogical purposes of documentary film in language classrooms as the processing of written texts is required before the production of a documentary film. Although documentary film has a strong relationship with writing skills and having access to these authentic materials are very easy, some educators ignore these authentic inputs. Thus this paper investigates the importance of using documentary film in enhancing the learning of Arabic as a second language with specific focus on writing skills. In addition, this paper examines local experts’ views on the utilization of documentary film in the Arabic as a second language classroom. A set of questionnaire with both open and closed-ended questions were distributed among twelve experts in the field of Arabic as a second language in Malaysian public universities. Feedbacks from the experts were collected and analyzed. The findings indicated strong recommendations from Arabic language experts in Malaysia. Among the recommendations are the types of documentary films to be utilized, the categories of writing skills that can be developed, and the appropriate instructional techniques to be used in the classroom. In general, this study hopes to contribute to the field of Arabic teaching language skills to non-native speakers and a useful reference for curriculum designers, ministry officials, textbook authors, and teachers.